PF.61 Starry Sky Pattern of Fetal Liver Associated with Twin Anaemia Polycythaemia Sequence in Monochorionic Twins. (26th April 2013) - Soundararajan, L; Howe, D
Abstract : Twin anaemia-polycythaemia sequence (TAPS) is an atypical form of twin-twin transfusion syndrome (TTTS) that presents as a large inter-twin haemoglobin difference with one twin developing anaemia and the other developing polycythaemia, without oligohydramnios-polyhydramnios sequence. The prenatal diagnostic criteria for TAPS require that the middle cerebral artery-peak systolic velocity (MCA-PSV) measure greater than 1.5 multiples of median (MoM) in the anaemic twin and less than 0.8 MoM in the polycythaemic twin. Starry-sky liver appearance was first described in 1980 by Kurtz et al, as corresponding to oedematous swelling of hepatocytes causing decreased echogenicity of the parenchyma (sky) as well as better visualisation of the fibrous walls of the portal vein (stars). We present a case of monochorionic diamniotic twins with spontaneous twin anaemia- polycythaemia sequence (TAPS) in which the rare sonographic appearance of starry sky liver was seen in the recipient (polycythaemic) twin. The polycythaemic twin had starry sky liver appearance from 25 weeks gestation prior to any sonographic features of TAPS. She was delivered at 28 weeks 6 days gestation when diagnosis of TAPS was made, due to deterioration in growth and Dopplers. One twin was anaemic with haemoglobin of 10.5 g/dl and the other polycythaemic with haemoglobin of 28.0 g/dl. Conclusion: In our case, starry sky appearance of the liver was the early sonographic feature of Twin anaemia polycythaemia sequence.